2014
DOI: 10.1186/1749-7922-9-47
|View full text |Cite
|
Sign up to set email alerts
|

Isolated dissection of the superior mesenteric artery treated using open emergency surgery

Abstract: BackgroundIsolated dissection of the superior mesenteric artery (IDSMA) remains a rare diagnosis. However, new diagnostic means such as computed tomography makes it possible to detect even asymptomatic patients. If patients present symptomatic on admission, the risk of bowel infarction makes immediate therapy necessary. Today, endovascular techniques are often successfully used; however, open surgery remains important for special indications. In this paper, we present two cases with IDSMA and show why open sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Contrast-enhanced CT findings are reported to be more useful than those obtained with plain CT to evaluate an existing lesion, intestinal wall thickness, and ascites [ 5 ], as plain CT results can mislead to a diagnosis of SMA dissection [ 4 ]. Reported characteristic CT findings of SMA dissection include thrombosis of a false lumen, an intimal flap, an enlarged SMA diameter, increased attenuation of fat around the SMA, and hematoma in the mesentery with hemorrhagic ascites [ 6 , 7 ]. However, it should be noted that not all cases necessarily have an intimal flap, and some show only an enlarged SMA diameter and increased attenuation of the fat around the SMA [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced CT findings are reported to be more useful than those obtained with plain CT to evaluate an existing lesion, intestinal wall thickness, and ascites [ 5 ], as plain CT results can mislead to a diagnosis of SMA dissection [ 4 ]. Reported characteristic CT findings of SMA dissection include thrombosis of a false lumen, an intimal flap, an enlarged SMA diameter, increased attenuation of fat around the SMA, and hematoma in the mesentery with hemorrhagic ascites [ 6 , 7 ]. However, it should be noted that not all cases necessarily have an intimal flap, and some show only an enlarged SMA diameter and increased attenuation of the fat around the SMA [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this period, 224 patients (117 CMI, 55 acute mesenteric ischemia, 29 median arcuate ligament syndrome, and 23 visceral artery aneurysms) were treated for visceral artery pathologies [12][13][14][15] . For this study, we identified 100 patients and 160 arteries with a relevant stenosis or occlusion of the TC or the SMA.…”
Section: Resultsmentioning
confidence: 99%
“…Although several treatment options, including conservative, endovascular, and surgical treatment, are available, there is currently no consensus regarding the optimal management of SISMAD. 1) 6) 13 14 15 16) …”
Section: Management Strategymentioning
confidence: 99%